From Greenland to Canada in Ten Days: Tracks of Bowhead Whales, Balaena mysticetus, across Baffin Bay - Heide-Jørgensen, M.P.; Laidre, K.L.; Wiig, Ø.; Jensen, M.V.; Dueck, L.; Maiers, L.D.; Schmidt, H.C.; Hobbs, R.C. (ARCTIC, 2003)
Five bowhead whales (Balaena mysticetus) were instrumented with satellite transmitters in northwestern Disko Bay, West Greenland, in May 2001. Best results were obtained when tags were deployed with a pole rather than a pneumatic gun. At least three of the tagged whales remained in the northwestern part of the bay for one to two weeks after tagging. A male and a female whale moved from Disko Bay to northern Canada. They left Disko Bay 11 days apart and took different routes across Baffin Bay to the southern part of the North Water polynya, just east of the entrance to Lancaster Sound. The whales crossed the central part of Baffin Bay relatively rapidly (travel time of 9-10 days, 3.1 and 4.5 km/h). Dive behaviour of one whale was monitored and showed changes in dive depths, dive rates, and surfacing times in different localities, indicating behavioural changes probably related to feeding. The whales were presumably feeding in both Disko Bay in May and in the southern part of the North Water (southeast of Bylot Island) in June. This study confirms whalers' observations that bowhead whales move between West Greenland and the east coast of Baffin Island. En mai 2001, cinq baleines boréales (Balaena mysticetus) ont été équipées d'émetteurs spatiaux dans le nord-ouest de la baie de Disko (Groenland occidental). Les meilleurs résultats ont été obtenus lorsque les marqueurs ont été apposés avec une perche plutôt qu'avec un fusil à air comprimé. Au moins trois des baleines marquées sont restées dans la partie nord-ouest de la baie pendant une à deux semaines après le marquage. Deux individus, un mâle et une femelle, se sont déplacés de la baie de Disko au nord du Canada. Ils ont quitté la baie à 11 jours d'écart et ont emprunté des trajets différents pour traverser la baie de Baffin et rejoindre la partie méridionale de la polynie de l'Eau du Nord, située juste à l'est de l'entrée du détroit de Lancaster. Les baleines ont traversé la partie centrale de la baie de Baffin assez vite (en 9 et 10 jours, soit 3,1 et 4,5 ...